The use of medications approved for alcohol use disorders in Italy - Fortinguerra, Filomena; Pierantozzi, Andrea; Trotta, Francesco (Frontiers in Public Health, 2023)
Abstract Background: Italy is among European countries with the highest per capita alcohol consumption. Several pharmacological treatments for alcohol use disorders (AUDs) are currently available in Italy but no consumption data are available. A first analysis on national drug consumption, covering the whole Italian population, on a long-term period covering the COVID-19 pandemic, was performed. Methods: To analyse the consumption of medications indicated for therapy of alcohol dependence different national data sources were used. Consumption was measured as defined daily dose (DDD) per 1,000,000 inhabitants per day. Results: During 2020 the total consumption of medicines used in the treatment of AUDs amounted to 310.3 DDD per 1 million inhabitants per day (0.018% of the overall drug consumption in Italy) with a decreasing gradient from the North (373.9 DDD) to the South (250.7 DDD). The 53.2% of the overall doses were dispensed by public healthcare facilities, 23.5% by community pharmacies, while the remaining 23.3% were purchased privately. The temporal trend of consumption seemed to be stable across the last years, although an impact of COVID-19 pandemic was observed. Disulfiram was the most consumed medicine over years. Conclusions: All Italian regions offer pharmacological treatments to patients with AUDs, but differences in number of dispensed doses suggest a different local organization of patient’s care, which can be partly explained by the different severity of the clinical condition of residing patients. Pharmacotherapy of alcoholism should be deeply investigated to describe the clinical characteristics of treated patients (i.e co-morbidities) and evaluate the appropriatess of prescribed medications.